ای کامرس اسلامی تعلیمات کی روشنی میں: ایک فقہی مطالعہ : E-Commerce in the Light of Islamic Teachings: A Jurisprudential Analysis - Dr. Hafiz Muhammad Asif Javeed, (Al Manhal Research Journal, 2024)
The advent of modern technology, including computers, the internet, and mobile networks, has revolutionized global commerce, transforming the world into a "global village." E-commerce, encompassing the buying and selling of goods and services through electronic systems, has emerged as a dominant mode of trade. As e-commerce spreads worldwide, many Muslims question its compatibility with Shariah (Islamic Law). This study explores the jurisprudential implications of e-commerce, focusing on its adherence to Islamic principles such as transparency, fairness, and the avoidance of prohibited elements like riba (interest), gharar (uncertainty), and haram (prohibited) goods and services. The research examines key aspects, including contract formation (‘Aqd), payment methods, and dispute resolution, within the framework of Shariah. It discusses business models like business-to-business (B2B), business-to-consumer (B2C), and business-to-government (B2G) while emphasizing the necessity of integrating Islamic ethics into e-commerce practices. The study is supported by evidence from the Holy Quran, the practices of Prophet Muhammad (peace be upon him), classical Fiqh literature, and resolutions of various Fiqh academies. The research analyzes the legality and ethical dimensions of e-commerce to provide guidance for Muslims to utilize this modern trade method in compliance with Islamic principles. It underscores the potential of e-commerce to improve the economic condition of Muslims globally, ensuring that trade aligns with Shariah standards. This integration offers a path for ethical and legal business practices in the rapidly evolving digital marketplace.